Equity Incentives and Corporate Fraud in China - Hass, Lars Helge (Journal of business ethics, 2016)
This paper explores how managers’ and supervisors’ equity incentives impact the likelihood of committing corporate fraud in Chinese-listed firms. Previous research has shown that corporate fraud in China is a widespread phenomenon and has severe consequences for affected firms and executives. However, our understanding of the reasons that fraud is committed in a Chinese setting has been very limited thus far. This is an increasingly important topic, because corporate governance is rapidly changing in China, and it is unclear whether adopting the executive compensation practices of the West is appropriate for Chinese firms. We show that managers’ equity incentives increase their propensity to commit corporate fraud. We also find that this effect is more pronounced for state-owned firms. However, we find a negative but not significant relationship between the equity incentives of the supervisory board and the incidence of fraud.